Reading Teachers: Reading Strategies Employed in Teaching Reading in Grade School - Sammy Dolba; Louie Gula; Jayrome Nunez (Journal of Language and Literature Studies, 2022)
The purpose of the study. The aims of this research are to determine the teachers' reading style, determine their reading speed, and determine which reading methods are the teachers' strengths and weaknesses utilizing a thorough evaluation of reading techniques from Hawker Brownlow Education. This study utilized the comprehensive assessment of reading strategies from Hawker Brownlow Education. This material is composed of four series of tests namely, Reading Comprehension 1- Historical Fiction, Reading Comprehension 2- History Article, Reading Comprehension 3- Kate Wrote About a Special Zoo, and Reading Comprehension 4- Email written by Carl with different reading passages using the same 12 reading strategies. It is found that readers can effectively comprehend when they use the following strategies namely, finding word meaning in context, understanding sequence, and making predictions. Therefore, the four series of assessments, show that there are varied ways of comprehending a material that might directly influence the duration and time limit allocated in reading and answering the material, the recurring events of the same material used, and the scheduling of reading comprehension tests.